Non-European immigrants' self-described strategies for mental health promotion and perceptions of Finnish mental health services: A qualitative descriptive analysis - Roth Minni; Lahti Mari; Gustafsson Noora; Berg Johanna; Kaitala Elina; Kuosmanen Lauri (WILEY, 2022)
Purpose: This study aims to describe non-European immigrants' perceptions toward mental health care in Finland and the factors that support their mental health.
Design and methods: Participants (N = 17) were interviewed through semistructured interviews, after which interview transcripts were analyzed using a six-phase thematic analysis process.
Findings: The participants reported that developing self-help strategies benefitted their mental health. The participants primarily preferred unprofessional help over professional mental health care. Several structural and cultural barriers to help-seeking were identified.
Practical implication: Health care staff working with immigrants need proper education and knowledge to provide sufficient, holistic care; for this reason, information about the cultural differences among immigrants and cultural sensitivity should be included in basic as well as post-graduate nursing education.
Keywords: Finland; immigrant;